2018
DOI: 10.1007/s11657-018-0504-y
|View full text |Cite
|
Sign up to set email alerts
|

Moderate-to-heavy smoking in women is potentially associated with compromised cortical porosity and stiffness at the distal radius

Abstract: Skeletal effects of smoking become evident at the micron level through a structurally and mechanically compromised cortical compartment, which partially explains the inconsistent results observed at the macro-level, and the poor clinical outcomes. Smoking may also compound postmenopausal effects on bone potentially placing women having undergone menopause at a greater risk for fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Cigarette smoke has many compounds harmful to the human body. 1 2 3 4 Nicotine is an addictive part contained in these cigarettes and has deleterious influence on many vital organs. 1 4 5 The effect of cigarette smoking on bone metabolism has been reported in many studies that observed that bone density is reduced in elderly and postmenopausal smokers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cigarette smoke has many compounds harmful to the human body. 1 2 3 4 Nicotine is an addictive part contained in these cigarettes and has deleterious influence on many vital organs. 1 4 5 The effect of cigarette smoking on bone metabolism has been reported in many studies that observed that bone density is reduced in elderly and postmenopausal smokers.…”
Section: Introductionmentioning
confidence: 99%
“…1 4 5 The effect of cigarette smoking on bone metabolism has been reported in many studies that observed that bone density is reduced in elderly and postmenopausal smokers. 3 6 Nicotine causes vasoconstriction and tissues hypoxemia, thus delaying fracture healing. 7 8 Nonunion, delayed union, and residual pain are the complications of smoking associated with fracture healing.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012 alone, the global cost of smoking-attributable diseases (excluding second-hand smoking) was equivalent to 5.7% of the global health expenditure [3]. In addition to being a risk factor for poor bone mineral density [4] and increased cortical porosity [5], the effects of smoking on periodontal health are well-documented [6,7]. Although dental rehabilitation using osseointegrated implants is a reliable treatment modality with high survival rates [8,9], smoking can modulate the expression of osteogenic and inflammatory factors in alveolar bone [10], implant-adherent cells [11], and in the peri-implant crevicular fluid [12,13].…”
Section: Introductionmentioning
confidence: 99%